Effect of flaxseed extract on the liver histological structure in streptozotocin induced diabetic rats - Al-Ani, Imad Matloub Dally; Abired, Ahmed N.; Mustafa Al-Ahmad, Basma Ezzat; Abdel Wahab, Emad Mohamad Nafie; Azzubaidi, Marwan Saad (Kulliyyah of Medicine, International Islamic University Malaysia., 2017)
Introduction: Diabetes mellitus has become a serious warning to mankind health all over the world. The management goal of diabetes is to keep blood glucose levels as close as possible to healthy individuals. Medications used to treat diabetes are usually associated with complications and may cause different side effects. Many traditional anti-diabetic plants have become popular in the management of diabetes mellitus. Flaxseed has been used as traditional medicine for centuries. Objective: This study aimed to evaluate the hepatoprotective effects of flaxseed extract in streptozotocin (STZ)-induced diabetic rats. Methods: Diabetes mellitus was induced in Sprague-Dawley rats using a single injection of streptozotocin (60 mg/kg i.p.). The rats were divided into five groups of 8 rats each. Group NC, normal control rats; Group NF, normal rats treated with flaxseed extract (400 mg/kg); Group DC, diabetic control rats; Group DG, diabetic rats treated with glibenclamide (0.6 mg/kg); Group DF, diabetic rats treated with flaxseed extract (400 mg/kg); for 4 weeks. Results: There were significant increase in relative liver weight, blood glucose levels in DC group comparing to NC group (p<0.05). The disturbance of these parameters was ameliorated in DF and DG groups. Histological observation revealed congestion of central veins, degeneration of hepatocytes, and reduced glycogen granules in DC group. These pathological changes were ameliorated in the flaxseed extract and glibenclamide treated rats. Conclusion: Flaxseed extract may represent a candidate alternative treatment to control diabetes mellitus and its related hepatopathy.